Cytokine response in asymptomatic and symptomatic Plasmodium falciparum infections in children in a rural area of south-eastern Gabon. - Sandrine Lydie Oyegue-Liabagui; Chérone Nancy Mbani Mpega Ntigui; Mérédith Flore Ada Mengome; Lady Charlene Kouna; Nathalie Pernelle Tsafack Tegomo; Neil Michel Longo Pendy; Jean-Bernard Lekana-Douki (PLoS ONE, 2023)
Plasmodium falciparum is a parasite that causes asymptomatic or symptomatic malaria infections in humans depending on various factors. These infections are also a major cause of anemia in intertropical countries such as Gabon. Past studies have clearly demonstrated that inflammatory markers such as cytokines play a key role in the pathogenesis of malaria disease. However, the clinical manifestations of severe malaria vary according to the level of transmission and more information is needed to gain a better understanding of the factors involved. As such, the objective of this study was to investigate the circulating levels of nine cytokines in asymptomatic and symptomatic P. falciparum infections in Gabonese children and their roles in the pathogenesis of anemia. Blood samples were collected from 241 children aged 3 to 180 months in Lastourville, south-eastern Gabon. Diagnosis of P. falciparum infection was performed using Rapid Diagnosis Tests, microscopy and nested PCR. Levels in the plasma of the Th1 (IFN-γ, TNF-α, IL-6 and IL-12p70), Th17 (IL-17A and IL-22) and Th2 (IL-10, IL-4 and IL-13) cytokines were measured by ELISA. Data showed that IL-6, IFN-γ, IL-12p70, IL-10, and IL-13 levels were significantly higher in children with symptomatic P. falciparum infection compared to uninfected children. IL-10 levels were significantly higher in symptomatic children than in asymptomatic children, who had moderately increased levels compared to uninfected controls. Moreover, only IL-10 and IL-6 levels were significantly higher in children with severe malarial anemia compared to children with uncomplicated malaria who had significantly lower IL-10 levels than children with moderate malarial anemia. These data indicate that the progression of P. falciparum infection towards an advanced stage in children is accompanied by a significant increase in type Th1 and/or Th2 cytokines. These inflammatory mediators could serve as potential predictors of anemia for malaria patients.